Samuel Phelps and Sadler's Wells Theatre (Wesleyan University Press, 1971)
Samuel Phelps (1804-1878) was an English actor and theater manager. In an era when performances of Shakespeare's works had been replaced with derived versions of themselves, Phelps became known for his exquisite productions of Shakespeare that were faithful to their original versions. Phelps revolutionized Shakespearean theatre when he took over management of Sadler's Wells Theatre and began showing productions of faithful reproductions. This is the definitive biography of the producer who brought the Shakespeare's original plays back to the forefront of theatre after over 100 years of derived versions. His exquisite reproductions revolutionized stage design and management. This is an especially important book for those interested in theatrical history and Shakespeare.